Prophetic niche in the virtuous city : the concept of Ḥikmah in early Islamic thought - Yaman, Hikmet. (Islamic Philosophy, Theology and Science. Texts and Studies, 2011)
This book analyzes the concept of ḥikmah in early Islamic texts within a network of multiple conceptual interrelationships in the cross-disciplinary context of Muslim works, roughly up to al-Ghazali's lifetime. The word ḥikmah has a wide spectrum of connotations in these texts, because it basically contains all knowledge within human reach, and accordingly, received a range of diverse scholarly treatments. This work contextualizes ḥikmah in a nuanced fashion in the collective usage of early Muslim authors, mainly by lexicographers, exegetes, philosophers, and Sufis. For the first time in the field of Arabic and Islamic Studies, particularly in Islamic Philosophy and Sufism, this study explores the concept of ḥikmah in an all-embracing capacity. Ḥikmah is a central concept of Islamic thinking, related to almost all intellectual disciplines of Muslim scholarly tradition, but it has been insufficiently underlined and treated in earlier western scholarship.